1997
DOI: 10.1159/000127175
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Synthase and cGMP in the Anterior Pituitary Gland: Effect of a GnRH Antagonist and Nitric Oxide Donors

Abstract: Using immunohistochemistry and in situ hybridization, it has been previously shown that gonadotropes and folliculo-stellate cells in the rat anterior pituitary gland express nitric oxide (NO) synthase (NOS), and that NOS expression is increased by gonadectomy. Using the indirect immunofluorescence technique in conjunction with antibodies raised to conjugated cGMP, we have attempted to establish the target cells for NO in the anterior pituitary and to define the mediator of NO regulation. After incubation of pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Using a direct in situ immunodetection technique to reveal cGMP-producing cells in response to NO donors in rat pituitary slices, Yamada et al (66) identified essentially gonadotrophs, suggesting that these cells primarily contained a functionally reactive sGC, or enough sGC to produce detectable levels of cGMP under these conditions. Surprisingly, in such studies no cGMP response to NO donors could be detected in folliculo-stellate cells (66). The same was recently observed by the McArdle's group (67) using a folliculostellate cell line (TtT-GF) and classical cGMP assay.…”
Section: Discussionmentioning
confidence: 99%
“…Using a direct in situ immunodetection technique to reveal cGMP-producing cells in response to NO donors in rat pituitary slices, Yamada et al (66) identified essentially gonadotrophs, suggesting that these cells primarily contained a functionally reactive sGC, or enough sGC to produce detectable levels of cGMP under these conditions. Surprisingly, in such studies no cGMP response to NO donors could be detected in folliculo-stellate cells (66). The same was recently observed by the McArdle's group (67) using a folliculostellate cell line (TtT-GF) and classical cGMP assay.…”
Section: Discussionmentioning
confidence: 99%
“…Sections were processed for immunocytochemistry as described (de Vente et al, 1996a,b;Yamada et al, 1997). Antisera used were a polyclonal sheep anticGMP (Tanaka et al, 1997; diluted 1:4000), a polyclonal rabbit anti-cGMP (de Vente et al, 1996a,b; diluted 1:300) and a polyclonal sheep anti-bNOS (kindly provided by Dr P.C.…”
Section: Bnos-and Cgmp-immunohistochemistry On Cryo-sectionsmentioning
confidence: 99%
“…Dilutions of the sera were made in filtered TBS supplemented with 0.3% Triton X-100. The specificity of these antisera in staining mammalian tissues has been largely demonstrated (de Vente et al, 1996a,b;Herbison et al, 1996;Tanaka et al, 1997;Yamada et al, 1997). In the single cGMP-immunostaining procedure, secondary antisera used were the CY3-labeled goat anti-rabbit IgG (Jackson; diluted 1:800) or the FITC-labeled rabbit anti-sheep (Calbiochem, La Jolla, CA; diluted 1:150), depending on the host species of the primary antiserum.…”
Section: Bnos-and Cgmp-immunohistochemistry On Cryo-sectionsmentioning
confidence: 99%
“…cGMP mediates NO effects on prolactin release (11). Although evidence for cGMP production in lactotrophs has not been obtained to date (33), our results indicate that this cyclic nucleotide participates in the regulation of prolactin release.…”
Section: Discussionmentioning
confidence: 47%